The pediatric disease spectrum in emergency departments across Pakistan: data from a pilot surveillance system. Issue 2 (December 2015) - Atiq, Huba; Siddiqui, Emaduddin; Bano, Surriya; Feroze, Asher; Kazi, Ghazala; Fayyaz, Jabeen; Gupta, Shivam; Razzak, Juanid; Hyder, Adnan; Mian, Asad
Abstract Background There is an increasing number of urgently ill and injured children being seen in emergency departments (ED) of developing countries. The pediatric disease burden in EDs across Pakistan is generally unknown. Our main objective was to determine the spectrum of disease and injury among children seen in EDs in Pakistan through a nationwide ED-based surveillance system. Methods Through the Pakistan National Emergency Department Surveillance (Pak-NEDS), data were collected from November 2010 to March 2011 in seven major tertiary care centers representing all provinces of Pakistan. These included five public and two private hospitals, with a collective annual census of over one million ED encounters. Results Of 25, 052 children registered in Pak-NEDS (10% of all patients seen): 61% were male, 13% under 5 years, while almost 65% were between 10 to < 16 years. The majority (90%) were seen in public hospital EDs. About half the patients were discharged from the EDs, 9% admitted to hospitals and only 1.3% died in the EDs. Injury (39%) was the most common presenting complaint, followed by fever/malaise (19%) and gastrointestinal symptoms (18%). Injury was more likely in males vs. females (43% vs. 33%; p < 0.001), with a peak presentation in the 5-12 year age group (45%). Conclusions Pediatric patients constitute a smaller proportion among general ED users in Pakistan. Injury is the most common presenting complaint for children seen in the ED. These data will help in resource allocation for cost effective pediatric ED service delivery systems. Prospective longer duration surveillance is needed in more representative pediatric EDs across Pakistan.